Nonsurgical management of a patient with multiple dens invaginatus affecting all maxillary incisors - Mostafa Ghandi; Farnaz Ghorbani; Davoud Jamshidi (Wolters Kluwer Medknow Publications, 2022)
This paper discussed a patient with dens invaginatus (DI) in all maxillary incisors that was accompanied by supernumerary tooth and also bifid cingulum, lingual pit, and talon cusp on the other teeth. DI is a rare developmental malformation usually seen in the maxillary lateral incisors of permanent dentition. A healthy 22-year-old Iranian woman was referred for the treatment of carious teeth. Following comprehensive clinical and radiographic examination, that was diagnosed DI affecting all maxillary central and lateral incisors. Left maxillary central incisor was Type I and the other incisors were Type II, according to Oehlers classification. Furthermore, she had supernumerary tooth and Class III malocclusion. All teeth responded to sensibility tests, except right maxillary central incisor that was diagnosed pulp necrosis and asymptomatic apical periodontitis. Conventional root canal therapy was done for the right maxillary central incisor using mineral trioxide aggregate and gutta percha and AH26 sealer by thermoplastic method. After 18 months of follow-up, clinical and radiographical examination revealed periapical healing of the right maxillary central incisor and absence of pulp and periapical pathosis in other incisors. The early recognition of DI, correct diagnosis, and appropriate management of this tooth is essential to ensure favorable treatment outcome.